Validation of treatment algorithm based on the Japan narrow-band imaging expert team classification for sub-centimeter colorectal polyps - Kato, Motohiko; Abe, Keiichiro; Kubosawa, Yoko; Sunata, Yukie; Hirai, Yuichiro; Hirata, Tetsu; Takada, Yoshiaki; Wada, Michiko; Takatori, Yusaku; Banno, Shigeo; Kinoshita, Satoshi; Mori, Hideki; Takabayashi, Kaoru; Kikuchi, Masahiro; Shiraishi, Junichi; Uraoka, Toshio (Endoscopy International Open, 2018)
Background and study aims Although cold polypectomy (CP) is widely used for colorectal polyps < 10 mm, appropriateness of indications for CP or endoscopic mucosal resection (EMR) are still unclear. The aim of this study was to validate the endoscopic treatment algorithm based on the Japan NBI Expert Team (JNET) classification.Patients and methods Consecutive patients with at least one colorectal non-pedunculated polyp < 10 mm between July 2014 and October 2016 were included in this retrospective study. During the period, EMR was performed for JNET ≥ 2B lesions and CP for JNET < 2A. Among a total of 3966 lesions, 3368 lesions with JNET ≤ 2A were resected by CP in compliance with the treatment algorithm but 565 resections for JNET ≤ 2A were not compliant (by EMR), while all 24 JNET > 2B lesions were removed by EMR in compliance with the algorithm. Polypectomy outcomes were compared between the compliant and non-compliant groups. Histological outcomes were analyzed in accordance with JNET classification.Results Post-polypectomy bleeding rate in the compliant group (0 %) was lower than that in the non-compliant group (0.53 %, P < 0.01). Proportion of lesions diagnosed as cancer (38 % vs 0.36 %, P < 0.01) or submucosal cancer (4.2 % vs 0.03 %, P = 0.012), and the lesion with free resection margin (91 % vs 64 %, P < 0.01) was higher in the JNET ≥ 2B than JNET ≤ 2A.Conclusion This study indicated our algorithm would be valid: CP is suitable for most polyps < 10 mm as incidence of post-polypectomy bleeding is low, whereas EMR is recommended for JNET ≥ 2B lesions for histological complete removal.